2022
DOI: 10.2147/ijnrd.s344725
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulus-on-a-Chip: Current Insights and Future Potential Towards Recapitulating Selectively Permeable Filtration Systems

Abstract: Glomerulopathy, characterized by a dysfunctional glomerular capillary wall, results in proteinuria, leading to end-stage renal failure and poor clinical outcomes, including renal death and increased overall mortality. Conventional glomerulopathy research, including drug discovery, has mostly relied on animal experiments because in-vitro glomerulus models, capable of evaluating functional selective permeability, was unavailable in conventional in-vitro cell culture systems. However, animal experiments have limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 102 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…All of them showed higher levels of albumin leakage than those in normal controls. Our results also revealed that serum exposure led to enhanced intercellular albumin diffusion in some IgAN and MN patients, similar to results of previous studies [15,38]. However, there was no statistically significant difference in the permeability of albumin in MCD and LN groups compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…All of them showed higher levels of albumin leakage than those in normal controls. Our results also revealed that serum exposure led to enhanced intercellular albumin diffusion in some IgAN and MN patients, similar to results of previous studies [15,38]. However, there was no statistically significant difference in the permeability of albumin in MCD and LN groups compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…The glomerulus chip model can be divided into the following mechanisms [ 12 ]. The first is a chip with a porous membrane, made from a polydimethylsiloxane plate with the porous membrane serving as the boundary for growing endothelium and podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Shear stress alone 34 , a combination of shear stress and cyclic straining cell adherent substrate 23 , and topographical micro-convex scaffold 25,35 have been reported to promote the podocyte maturation through maturation marker expression and/or cellular process elongation of podocytes compared to conventional static culture. 36 Meanwhile, glomerular filtration flow is generated upon hemofiltration and is considered a vertical shear stress acting on the podocyte. It is distinct from the horizontal shear stress because it is a force pulling away from basal to apical side for the cell.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%